The Effects of Flavonoid Extract from Capparis spinosa L. on Some Biological Parameters in Adult Male Albino Rats - Jamal Ali, Sarrah; F. Hamad, Sumaya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This study aimed to explain the effect of the flavonoid extract of Cappairs Spinosa on the body weight, lipid profile, glucose, and kidney functions of male rats. We extracted the plant material using methanol at 85% in the Soxhlet apparatus for 8 hours and fractionated it with ethyl acetate. Twenty adult male rats were used in this study, which was divided into four groups (5 rats/group); the first group (T1) received 10 mg/kg. The second group (T2) received 20 mg . The third group (T3) received 40 mgorally for 30 days, and the 4th group (control) received orally distal water. At the end of the experiment, we collected blood samples by cardiac puncture to measure blood sugar level, lipid profile, and kidney function parameters. The levels of blood cholesterol, triglycerides, and very-low-density lipoprotein (VLDL) all went down significantly in all treated groups. On the other hand, the level of high-density lipoprotein (HDL) went up significantly compared to the control group. The blood sugar result explained a significant reduction in all treated groups compared with the control group. When kidney function parameters were measured, the amounts of urea, creatinine, and uric acid were significantly lower in animals that were given the flavonoid extract compared to those that were not. The result shows that extracts affect a significant decrease in body weight compared with control rats. These results of biological parameters explained that there were significant (P≤0.05,P≤0.01).